"Behold this Creature's form and State": Katherine Philips and the Early Ascendancy. Issue 3 (3rd July 2017) - Morrissey, Lee
ABSTRACT: This essay proposes an explanation for the shift in Katherine Philips's work after the Restoration: she moved to Dublin. In the Dublin of the early 1660s, Philips found herself in what Mary Louise Pratt calls a "contact zone". With a large domesticated but physically imposing animal, Philips hit on a metaphor for a new relationship between Ireland and Britain. "The Irish Greyhound" embodies this new relationship and reflects her ability to build relationships between the two islands. In this way, she took an "archipelagic" approach to English literature, avant la lettre, and she has recently been recuperated in these terms by John Kerrigan, Marie-Louise Coolahan, Sarah Prescott and others. Philips's poetry formed part of the process of finding a new vocabulary for inter-island understanding. Although she wrote poems and letters about the leading families of contemporary Dublin, her "shaggy dog" poem has the advantage of being legible without decoding noms de plume or the political standing of her many Dublin friends.